Phylogenetic Relationships of Isognomon (Lightfoot, 1786) Oysters from North Sulawesi, Indonesia - Wullur, Stenly; Rumampuk, Natalie Detty; Tilaar, Sandra Olivia; Tindi, Monalisa; Smolak, Radoslav (Universitas Diponegoro, 2024)
The Isognomon (Lightfoot, 1786) is a genus of oysters found in various coastal ecosystems throughout the world. Along with other bivalves, it performs significant ecological functions in marine ecosystems by providing food and habitat for fish and invertebrate habitats, filtering water, and protecting shorelines. Taxonomic classification of the Isognomon oyster can be challenging due to the varied or cryptic phenotypic characters, particularly shell characters. In this study, two specimens with different shell characters of Isognomon oyster were collected from mangrove waters in Likupang, North Sulawesi, Indonesia, and subjected to molecular analysis to determine their identity. The mitochondrial cytochrome C oxidase subunit I (COI) gene was utilized as a primer for this purpose, and the genetic distance and phylogenetic position of the two specimens were determined by comparing them with the GenBank database. The Basic Local Alignment Search Tool (BLAST) revealed that the two specimens were of belonged to Isognomon ephippium, with a similarity of 99.84%. The genetic distance between the two specimens was calculated using the Tamura Nei model and found to be 0.00, while the genetic distance between I. ephippium and other species in the Isognomon genus ranged from 0.00 to 0.14. The results of the Neighbor Joining (NJ) tree analyses showed that the two specimens clustered together with I. ephippium, which was divided into two distinct clades with a strong bootstrap value of 100 at the node